A 30‐Year‐Old Man with Three Primary Malignancies: A Case of Constitutional Mismatch Repair Deficiency. Issue 1 (2017) - Rengifo‐Cam, William; Jasperson, Kory; Garrido‐Laguna, Ignacio; Colman, Howard; Scaife, Courtney; Samowitz, Wade; Samadder, Jewel N.
ABSTRACT : N/A: Constitutional mismatch repair deficiency (CMMRD) is a devastating cancer predisposition syndrome for which clinical manifestations, genetic screening, and cancer prevention strategies are limited. We report a case of CMMRD presenting with metachronous colorectal cancer and brain cancer. Oncologists and gastroenterologists should be aware of the CMMRD syndrome as a rare cause of very early‐onset colorectal cancer.